2008
DOI: 10.3174/ajnr.a1379
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Hydrocephalus after Gamma Knife Radiosurgery for Vestibular Schwannoma: An MR Imaging Study

Abstract: SUMMARY: Vestibular schwannomas are common, and gamma knife radiosurgery is a treatment option of symptomatic tumors. Hydrocephalus may be a complication of gamma knife treatment of vestibular schwannoma, though the cause-and-effect relationship can be debated because tumors can cause hydrocephalus without treatment. We present an MR imaging study of an unusual case of communicating hydrocephalus after gamma knife radiosurgery of a vestibular schwannoma in which the timeline of events strongly suggests that ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It has been suggested that communicating hydrocephalus accompanying VS is caused by tumor necrosis with subsequent CSF protein elevation. [16] Elevated CSF protein levels may lead to CSF malabsorption at the level of the arachnoid granulations. [17] The lumbar CSF protein concentration in all the 92 patients was analyzed, and hydrocephalus was reported to be related to high protein levels in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that communicating hydrocephalus accompanying VS is caused by tumor necrosis with subsequent CSF protein elevation. [16] Elevated CSF protein levels may lead to CSF malabsorption at the level of the arachnoid granulations. [17] The lumbar CSF protein concentration in all the 92 patients was analyzed, and hydrocephalus was reported to be related to high protein levels in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that communicating HCP accompanying VS is caused by tumor necrosis with subsequent CSF protein elevation. 5,7 Elevated CSF protein levels may lead to CSF malabsorption at the level of the arachnoid granulations. 3,6,12,13 Some investigators have suggested that obstructive or communicating HCP is significantly correlated with increasing tumor size, however, we found no such correlation in our population.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5,11 With an increasing number of patients presenting with VS, and those who are treated using GKS in particular, understanding the pathogenesis of the development of HCP is crucial for the management of these patients. It has been suggested that communicating HCP accompanying VS is caused by tumor necrosis with subsequent CSF protein elevation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between vestibular schwannoma (VS) and hydrocephalus represents 3.7% to 18% of all cases of VS. More frequently, it is a communicating type hydrocephalus [5] [6]. In our study, the prevalence of this pathological as- …”
Section: Frequencymentioning
confidence: 97%